An investigation into the short term and medium term health impacts of personal incapacitant sprays. A follow up of patients reported to the National Poisons Information Service (London). Issue 5 (25th August 2004) - Euripidou, E; MacLehose, R; Fletcher, A
Abstract : Objectives: The aim of this study is to describe the pattern of ill health after personal incapacitant spray (PIS) exposures reported to the National Poisons Information Service—London (NPIS-L) and the Chemical Incident Response Service and to evaluate the relation between sub-categories of PIS exposure and adverse health effects. Methods: Case series study of patients reported to the NPIS-L, by attending medical personnel during the period 16 January to 31 September 1998. Data collected by questionnaire sent to these medical personnel. Results: Several "adverse" symptoms, particularly dermatitis and blisters were reported for cases exposed to police PIS. These cases were more frequent than in those people exposed to non-police PIS. Adverse effects occurring more than six hours after exposure were also observed, which is in conflict with the recorded immediate, short lived, and self limiting symptoms that PIS are designed to cause. Most patients with persisting symptoms required further treatment. Conclusions: These findings suggest that the formulation of CS (o-chlorobenzylidine malononitrile) with MiBK (methyl iso-butyl ketone) used by the police is more harmful that has been previously assumed. If confirmed then the continued use of this formulation should be reviewed because of longer duration of adverse effects. Less concentrated formulations may reduce the severity or persistence of the adverse effects.